Inverse association between diabetes and altitude: A cross‐sectional study in the adult population of the United States. (28th May 2014) - Woolcott, Orison O.; Castillo, Oscar A.; Gutierrez, Cesar; Elashoff, Robert M.; Stefanovski, Darko; Bergman, Richard N.
<x xml:space="preserve">Abstract</x> Objective To determine whether geographical elevation is inversely associated with diabetes, while adjusting for multiple risk factors. Methods This is a cross‐sectional analysis of publicly available online data from the Behavioral Risk Factor Surveillance System, 2009. Final dataset included 285, 196 US adult subjects. Odds ratios were obtained from multilevel mixed‐effects logistic regression analysis. Results Among US adults (≥20 years old), the odds ratio for diabetes was 1.00 between 0 and 499 m of altitude (reference), 0.95 (95% confidence interval, 0.90‐1.01) between 500 and 1, 499 m, and 0.88 (0.81‐0.96) between 1, 500 and 3, 500 m, adjusting for age, sex, body mass index, ethnicity, self‐reported fruit and vegetable consumption, self‐reported physical activity, current smoking status, level of education, income, health status, employment status, and county‐level information on migration rate, urbanization, and latitude. The inverse association between altitude and diabetes in the US was found among men [0.84 (0.76‐0.94)], but not women [1.09 (0.97‐1.22)]. Conclusions Among US adults, living at high altitude (1, 500‐3, 500 m) is associated with lower odds of having diabetes than living between 0 and 499 m, while adjusting for multiple risk factors. Our findings suggest that geographical elevation may be an important factor linked to diabetes.